Preparing Arabidopsis thaliana root protoplasts for cryo electron tomography - Sanchez Carrillo, Ingrid Berenice; Hoffmann, Patrick C.; Barff, Teura; Beck, Martin; Germain, Hugo (Frontiers in Plant Science, 2023)
The use of protoplasts in plant biology has become a convenient tool for the application of transient gene expression. This model system has allowed the study of plant responses to biotic and abiotic stresses, protein location and trafficking, cell wall dynamics, and single-cell transcriptomics, among others. Although well-established protocols for isolating protoplasts from different plant tissues are available, they have never been used for studying plant cells using cryo-electron microscopy (cryo-EM) and cryo-electron tomography (cryo-ET). Here we describe a workflow to prepare root protoplasts from Arabidopsis thaliana plants for cryoelectron tomography. The process includes protoplast isolation and vitrification on EM grids, and cryo-focused ion beam milling (cryo-FIB), with the aim of tilt-series acquisition. The whole workflow, from growing the plants to the acquisition of the tilt series, may take a few months.Our protocol provides a novel application to use plant protoplasts as a tool for cryo-ET an dtilt series acquisition.